2020
DOI: 10.1111/ajco.13476
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19: What is the best approach in gynecological oncology patient management during the coronavirus pandemic?

Abstract: Coronavirus (COVID-19) infection is a new major concern and a global emergency in almost all countries worldwide; due to the higher sensibility of cancer patients, they are more susceptible to severe and fatal infections, being nearly 10 times more likely than in healthy individuals infected with this virus. Although the aggressive nature of a cancer is a matter of concern, our exact role as oncologists in this time of restricted resources is not fully clarified. Regarding some consensus recommendation for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Given the rapid evolution of evidence, recommendations, policies and clinical management adaptations, a rapid review on the current evidence and recommendations is highly warranted. Since the COVID-19 pandemic was declared, several publications have appeared providing narrative reviews in order to bring all the relevant information from the guidelines together in one document, to support patient care [8][9][10]. These studies summarise and review published guidelines, original studies, consensus statements, opinions and comments in peerreviewed journals, and professional organisations and societies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid evolution of evidence, recommendations, policies and clinical management adaptations, a rapid review on the current evidence and recommendations is highly warranted. Since the COVID-19 pandemic was declared, several publications have appeared providing narrative reviews in order to bring all the relevant information from the guidelines together in one document, to support patient care [8][9][10]. These studies summarise and review published guidelines, original studies, consensus statements, opinions and comments in peerreviewed journals, and professional organisations and societies.…”
Section: Introductionmentioning
confidence: 99%
“…Women who experience fear and anxiety about COVID-19 infection use CAM methods to fight the disease and increase immunity and hope. It is thought that reduction in hospital visits and interruption of treatment, due to the pandemic [1] , [6] , [11] , caused patients with gynecological cancer to opt for CAM methods to help control their conditions. In the literature, no similar studies on this subject have been found.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is thought to be especially stressful for cancer patients [6] , [8] , [9] , [10] . The literature shows that cancer patients have a higher risk of death due to COVID-19; the level of admission to intensive care units is high; and they need more invasive ventilation, compared to non-cancer patients [3] , [11] . During the pandemic, cancer patients cancelled or postponed elective and non-emergency cancer surgeries and medical tests due to concerns over these negative health outcomes, and changes in treatment protocols were made (e.g., longer intervals between chemotherapy cycles) [1] , [2] , [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many medical professional societies quickly released updated guidelines to support clinicians (the SGO, the British Gynecologic Oncology Society, etc.) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%